Lo que los gestos dicen y las palabras callan: una entrevista con Clinton - Gloria Álvarez-Benito; Isabel M. Íñigo-Mora (Philologia Hispalensis, 2012)
This paper focuses on the study of televised interviews, a field of which there is a vast amount of literature (Bull and Elliot 1998; Carter and Mccarthy 2002; Clayman 1988, 1991, 1992, 1993; Greatbatch 1986, 1988, 1992; Harris 1986, 1991; and Heritage and Greatbatch 1991). Our objective is to analyse the use of verbal and nonverbal elements as communicative strategies in polit- ical interviews and more specifically in a televised interview with the ex-Presi- dent of the United States, Bill Clinton. We will attempt to discover the way in which politicians try to take advantage of verbal and nonverbal signals in tel- evised interviews.